Adherence to the Mediterranean diet in Turkish hospitalized older adults and its association with hospital clinical outcomes. (March 2022) - Ergul, Fatih; Sackan, Fatih; Koc, Ahmet; Guney, Ibrahim; Kizilarslanoglu, Muhammet Cemal
Highlights: According to the EDI score of hospitalized patients in our country, approximately 91.5% are in the unhealthy diet group. The EDI score is associated with the malnutrition and frailty of the older inpatients at the time of hospitalization. The EDI score is an independent parameter associated with frailty during hospitalization of older inpatients. The worse the adherence to the Mediterranean type diet in hospitalized patients due to infectious diseases, the longer the hospital stay. Patients with good adherence to the Mediterranean type diet are less likely to have recurrent emergency department admissions. Abstract: Aim: To identify the Mediterranean diet adherence in Turkish older inpatients and its relation to clinical outcomes. Methods: A total of 200 hospitalized patients over 60 years old (mean age; 72.9 ± 8.5 years, 59.5% female) were included in the study. Beside evaluating the demographic properties, they were evaluated by Elderly Dietary Index (EDI), Mini-nutritional assessment-short form (MNA-SF), and FRAIL index. Length of hospital stay, need of intensive care, and hospital clinical outcomes were also recorded. Results: According to the EDI scoring, the rate of unhealthy diets among study population was 91.5% and 56% of the patients were frail and 17% were malnourished. EDI score was significantly and positively correlated with height (rho=0.183), weight (rho=0.142), MNA-SF score (rho=0.204), glomerular filtration rate (GFR) (rho=0.152), and alanine-aminotransferase (ALT) (rho=0.278) levels ( p  = 0.009; 0.046; 0.004; 0.032; and <0.001, respectively). EDI scores were higher in male and married patients when compared to female and widow ones ( p  = 0.001 and 0.023, respectively). There was a negative, moderate, and statistically significant correlation between EDI score and length of hospital stay in patients hospitalized for infectious diseases (rho:-0.510; p  = 0.036). EDI score was also significantly related to frailty status ( p  = 0.017) and malnutrition ( p  = 0.026). The EDI score was found to be an independent parameter for frailty in a regression analysis model (OR=0.826;%95 CI: 0.713–0.959; p  = 0.012). Conclusion: It was shown that hospitalized older adults had a low adherence to the Mediterranean diet. Unhealthy diet group might be associated with poor clinical outcomes such as malnutrition, frailty, increased length of hospital stay, and recurrent emergency department admissions.